Antioxidant status and lipid peroxidation in seminal plasma and spermatozoa of patients with ankylosing spondylitis - Ozgocmen, S; Sogut, S; Fadillioglu, E; Ardicoglu, A; Ardicoglu, O (Oxford Univ Press, 2003)
[Abstract Not Available]